Strategies for Strengthening Student Organizations in Developing Students’ Soft Skills: A Systematic Literature Review - Mahaphiyi Hama; Raharjo; Agus Nur Hadi (Journal of Counseling, Education and Society, 2025)
Soft skills development has become a major concern in higher education in preparing students to respond to changing social and professional demands. Student organizations have considerable potential as non-formal learning environments in which students gain practical experience in communication, teamwork, leadership, problem-solving, and decision-making. This study aims to analyze and synthesize strategies for strengthening student organizations to develop students’ soft skills. The study employed a Systematic Literature Review (SLR), with the literature selection and reporting process guided by PRISMA 2020. Relevant literature was retrieved from Scopus, Web of Science (WoS), DOAJ, Google Scholar, and SINTA using keywords related to student organizations, student engagement, leadership, extracurricular activities, soft skills, and employability. Following the identification, screening, eligibility, and inclusion stages, 30 eligible articles were analysed using thematic analysis and narrative synthesis. The synthesis identified five major strategies: strengthening organizational structures, strengthening work programs, fostering organizational culture, strengthening mentoring and developmental support systems, and expanding organizational networks. These findings indicate that soft skills development is determined not merely by students’ participation in organizations, but more importantly by the quality of learning experiences, the level of student engagement, reflective and mentoring processes, and opportunities to interact with social and professional environments. This review proposes a conceptual framework that positions student organizational strengthening as a non-formal learning ecosystem operating through student engagement and experiential learning to foster soft skills development and graduate employability. The findings imply that higher education institutions should shift the management of student organizations from an activity-oriented approach toward competency-oriented organizational development.